Development and validation of authentic assessment to assess higher order thinking skills - Razmawaty Mohamed (2020)
The purpose of the study was to develop and validate an authentic assessment module to assesshigher order thinking skills. This study used Collect-Relate-Create-Donates (CRCD) model by BenShneiderman as the basis for the contents of the module. The module was developed by usingADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Thismodule underwent validation process using Fleiss' Kappa agreement coefficient by eightexperts. This study was also designed to determine the effect of the module towards higherorder thinking skills (HOTS) amongst the students in terms of their reasoning and problemsolving. A sample of 30 students was selected from a secondary school in Selangor. This studyinvolved the administration of pre- and post-tests on the 30 form four Biology students. The modulewas conducted during Biology lesson for 12 weeks. The validation showed that Fleiss' Kappaagreement coefficient for face validation is 0.63 which is at substantial agreement and0.89 (almost perfect agreement) for content validation. The students were given pre- and post-testswhich consisted of HOTS items adapted from Examinations Syndicate. The pre- and post-tests alsoincluded items that measured the students' ability in problem-solving and reasoning. The datashowed that the mean for the post-test (M = 21.20; SD = 4.96) was higher than the mean for pre-test(M = 12.07; SD = 3.59). Hence, the data showed that there was an increase in mean scores of thepost-test compared to the pre-test. Students have shown improvement in HOTS after using themodule. In conclusion, the authentic assessment module was effective in enhancingstudents' ability in HOTS particularly in reasoning and problem-solving. This implicatesthat the use of the authentic assessment module can be expanded toform four students in other schools to assess their higher order thinking skills.